Association between HLA-A1 and -A2 types and Epstein–Barr virus status of post-transplant lymphoproliferative disorder. Issue 10 (2nd October 2016) - Kinch, Amelie; Sundström, Christer; Tufveson, Gunnar; Glimelius, Ingrid
Abstract: The susceptibility to Epstein–Barr virus (EBV)-related post-transplant lymphoproliferative disorder (PTLD) may be affected by the human leukocyte antigen (HLA) type. We investigated HLA-A and HLA-B allele frequencies, focusing on HLA-A1 and -A2, in a population-based case series of EBV + ( n  = 60) and EBV− ( n  = 44) PTLD after solid organ transplantation. The proportion of EBV + PTLD was highest in HLA-A1 homozygotes (100%), lower in carriers of HLA-A1/AX (79%), HLA-A1/A2 (55%), HLA-A2/AX (54%), and lowest in HLA-A2 homozygotes (37%). HLA-A1 type was overrepresented (22% versus 7%, p  = 0.05) and HLA-A2 type underrepresented (57% versus 80%, p  = 0.01) in patients with EBV + compared with EBV − PTLD. EBV + PTLD in HLA-A1 carriers developed almost exclusively in already EBV-seropositive individuals. EBV status of PTLD was not related to any other HLA-A or HLA-B type. Our findings suggest that HLA-A1 carriers may have an increased risk of EBV + PTLD due to a decreased ability to control the latent EBV infection.